Pengaruh Framing Niat Terhadap Persistensi Dalam Mengerjakan Tugas Sulit Pada Mahasiswa Psikologi UIN Raden Fatah Palembang - Chintia Viranda; Lili Yanti, Zahwa; Rediansyah; Reisha Pratishifa; Diva Mulyafajri; Putri Deah; Sherly Oktavia (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
This study aimed to determine the effect of intention framing on students' persistence in completing difficult tasks. Persistence is defined as an individual's ability to maintain effort and continue working on a task despite encountering obstacles and challenges. This study employed an experimental method using a Posttest Only Control Group Design. The participants consisted of 20 Psychology students of UIN Raden Fatah Palembang, divided into an experimental group (n = 10) and a control group (n = 10). The experimental group received a positive intention framing intervention before completing a series of difficult logical reasoning tasks, while the control group received no intervention. Persistence was measured using ten logical reasoning questions designed to assess participants' willingness to continue working on challenging tasks. Data were analyzed using an Independent Sample t-Test. The results indicated a significant difference between the experimental and control groups (p < 0.05). Participants in the experimental group demonstrated higher persistence scores than those in the control group. These findings suggest that intention framing positively influences students' persistence in completing difficult tasks.